Magistrates marching in the streets: making and debating judicial independence and the rule of law in Benin. Issue 3 (September 2022) - Kolloch, Annalena
Abstract: Since 2012, judges and prosecutors in Benin have repeatedly protested against political interference and demanded compliance with their statutorily guaranteed independence. In 2014 and 2017, magistrates demonstrated in their judicial robes in the streets, protesting against the government's bill to deprive them of their right to strike and other freedoms. Benin has been described as a 'success story of democracy' (Stroh and Never, 2006, p. 1) and even as a 'model democracy' (cf. Kohnert, 1996, p. 78; Magnusson, 2001, p. 211; Bierschenk, 2009 ) since its peaceful transition to democratic conditions and its participation in a national conference in 1990/91. So why were magistrates in Benin demonstrating in the streets for the first time in the history of their profession? Based on fieldwork in Benin in 2009 and 2015 and archival research in 2017 in France, my paper analyses the change in the style of interactions between parts of the executive and parts of the judiciary in the history of the profession – a change from political negotiation to confrontation. Through their strikes and industrial action, magistrates fought for judicial independence; yet, at the same time they constructed legality and strengthened democracy because their actions emphasised the rule of law. My paper also considers the specifics of their strikes in the context of other striking civil servants. When magistrates, as bureaucrats, become politically active, it marks a transformation in their self-conception, as they are usually reserved and withdraw themselves from political and public spheres.